Residential mobility and receipt of measles, mumps and rubella vaccination: analysis of linked primary care electronic health records in a London region - Firman, Nicola; North, Laura; Marszalek, Milena; Wilk, Marta; Gutierrez, Ana; Johnson, Rhodri; Dezateux, Carol (International Journal of Population Data Science, 2026)
Background Residential mobility in early life may disrupt access to health care. We examined associations between residential mobility in the first two years of life and receipt of first measles, mumps and rubella (MMR) vaccination by 24 months of age. Methods We analysed electronic health records for children born between 01/01/2014 and 30/10/2019 and registered with primary care general practices (GPs) in north-east London (NEL). Primary outcome was receipt of first MMR vaccination between 12 and 24 months of age and residential mobility was defined by number of GP-recorded addresses by vaccination date or 24 months of age. We used logistic regression to estimate the odds ratio (OR) and 95% confidence intervals (CI) of receipt of MMR vaccination by residential mobility, adjusting for sex, ethnicity, number of children in the household, household composition, area-level deprivation, and local government area of residence. Results We included 150,949 children (51.0% boys) of whom 127,958 (84.8%) had received a first MMR vaccination and 22.3% had more than one GP-recorded address. Compared to children with one GP-recorded address, children with multiple GP-recorded addresses were at higher risk of not receiving their first MMR vaccination by 24 months of age. Those with two GP-recorded addresses had a 54% increased likelihood (OR: 0.46; 95% CI: 0.44,0.48), and those with three or more GP-recorded addresses a 68% increased likelihood (0.32; 95% CI: 0.29,0.36), compared to those with one. Conclusions Children who change address in early life are less likely to be protected against measles and other infections. Measles outbreaks in the UK have been in urban areas with high residential mobility and low MMR vaccine uptake suggesting the need for review of the immunisation status of children newly registered with GPs.